Praktik Vegetarian sebagai Etika Lingkungan yang Dihayati dalam Keluarga Buddhayana Indonesia - Komala, Nurma Syelin (LPPM STIAB JINARAKKHITA LAMPUNG, 2025)
As religious traditions are called to address the climate crisis, the impact of food systems is often overlooked. A plant-based diet (vegetarianism) emerges as a critical ecological action, yet it requires deep spiritual grounding in Indonesia. This article argues that this grounding is found within Mahayana Buddhist ecotheology through the ideal of the Bodhisattva. Using a qualitative case study method, this research examines Keluarga Buddhayana Indonesia (KBI). Data were collected through in-depth interviews and digital observation, then analyzed using thematic analysis guided by the hermeneutic spiral. The findings reveal how the Bodhisattva path rooted in the principles of ahiṃsā (non-harming), paṭiccasamuppāda (dependent origination), and karuṇā (active compassion), provides a compelling ethical basis for vegetarianism. This study concludes that the practice can be framed as an authentic expression of faith and an embodiment of the Bodhisattva's vow to liberate all beings from suffering.